PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 011 BANJAR XII KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Indrawati, Henny; Haryana, Gani; ', Jusnidar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The learning model Think Pair Share (TPS) provides an opportunity for each student to demonstrate the participation of others, working alone and in collaboration with others, so expect the students to be more active in the learning process in the classroom The aim of this study was to determine the improvement of learning outcomes IPS by applying cooperative learning model Think Pair Share (TPS) in class VA SD Negeri 011 XII Banjar Tanah Putih Rokan Hilir. The sample used is graders VA SD Negeri 011 XII Banjar Tanah Putih Rokan Hilir by the number of students 22 people, consisting of 9 male students and 13 female students. Data obtained by using observation and learning teshasil. Data analysis technique used is descriptive statistics: teacher and student activity analysis and analysis of achievement test. From the results of data analysis that has been done shows cooperative learning model Think Pair Share (TPS) can improve learning outcomes IPS Elementary School fifth grade students on the material XII 011 Banjar Indonesian Independence Struggle preparing the 2015/2016 school year. From these results it is expected that the school, the principal should give attention to cooperative learning model Think Pair Share (TPS), which is used by the teacher in the learning process for cooperative learning model Think Pair Share (TPS) can improve learning outcomes. If the result of learning increases, the quality of schools also increased.Keywords: TPS Learning Method , Results Learning.